Challenges faced by dental undergraduates during clinical training: A qualitative study - Vaibhav Gupta; K M Shwetha; Pushpanjali Krishnappa; K Sneha Shenoy (Wolters Kluwer Medknow Publications, 2016)
Introduction: Dental health-care professionals are expected to provide a wide range of dental care contributing to the quality of their patient's day-to-day lives, for which they are trained clinically during undergraduate (UG) course. Owing to scarcity of literature pertaining to challenges faced by dental UGs during their clinical training, research was conducted. Aim: The aim of this study was to assess challenges faced by dental UGs during the first patient encounter with patients in clinical posting. Materials and Methods: Four focused group discussions (FGDs) were conducted among 34 dental UGs using an FGD guide to facilitate the discussion process. A phenomenological approach was used to explore the lived experience of UGs. The recorded data were transcribed, translated, anonymized, and coded using Qualitative Data Analysis Miner software. Results: UGs were facing challenges related to communication, professionalism, and ethics every other day while treating patients. FGD conducted was able to explore the challenges faced by UGs during clinical posting such as language barrier, optimum utilization of material, and uphold confidentiality. Conclusions: Improving current state of UGs by taking care of all the mentioned challenges will help them become professionals with good communication skills.